Association between oxidative balance score and abdominal aortic calcification among middle-aged and elderly population - Zongao Cai; Jiachen She; Shuang Guo; Ruihui Li; Hairong Zhang; Xueli Guo; Shiyong Wu (BMC Cardiovascular Disorders, 2024)
Abstract Background The Oxidative Balance Score (OBS) was created to evaluate an individual’s overall antioxidant status. The objective of this study was to examine the association between OBS and abdominal aortic calcification (AAC) among individuals aged ≥ 40 years. Methods This population-based cross-sectional study used data from the National Health and Nutrition Examination Survey in 2013–2014 and included adults aged ≥ 40 years. Survey-weighted multivariable logistic and restricted cubic spline models were used to assess the association between OBS and AAC. Results Among 2520 participants, 744 were diagnosed with AAC (weighted percentage, 28.13%). Survey-weighted multivariable logistic revealed an inverse association between OBS and AAC [0.98 (0.96, 1.00)], and the nonlinear dose-response relationship was observed. Subgroup analysis and interaction tests revealed that this inverse relationship was consistent across different populations (all P for interaction > 0.05). Conclusions OBS was inversely associated with the prevalence of AAC among individuals aged ≥ 40 years. Maintaining a higher OBS may be beneficial in reducing the burden of AAC.